(untitled) (Research, Society and Development, 2022)
This study aimed to give an overview on the international scientific production on molar-incisor hypomineralisation and to analyze the 100 most-cited articles. A search strategy was built to retrieve the international scientific production on molar-incisor hypomineralisation in the Web of Science database up to July 2020. The 100 most-cited MIH articles were also identified. Two researchers performed article selection and data extraction. Graphical bibliometric maps were created at VOSviewer. A total of 292 MIH studies were included. Australia (51.0%) and Brazil (47.0%) were the countries with most articles. The University of Melbourne had the highest number of publications (18.5%). The 100 most-cited molar-incisor hypomineralisation articles received a mean of 32.01 citations. Most articles were published between 2013 and 2016 (52.0%). The most frequent topic was about prevalence of molar-incisor hypomineralisation (30.0%) and cross-sectional (45%) was the most frequent study design. No significant correlations were found between the journal Impact Factor (2019) and the total citations on WoS (p=0.076) and Google Scholar (p=0.411). This bibliometric study identified the global trends about molar-incisor hypomineralisation research activity.